O cooperativismo como base de apoio à agricultura familiar no município de Turvo - PR - Bastos, Tatiane Leal (2014)
The municipality of Turvo located in the mesoregion Center-South of Parana, presents environmental characteristics very relevant, as the remaining forest filled with araucarias. In addition, Turvo also is characterized by the development of agricultural activities introduced in the municipality by European immigrants, even at the beginning of their occupation. These immigrants generally cultivated in addition to plowing, a model productive social and cultural characteristic, represented by system faxinal, that was linked to the sustainable production process. Despite this, economic activities such as the extraction of wood and the modernization of agricultural techniques have reduced the native forests of the region. In this context was founded the IAF- Institute Agroflorestal Bernardo Hakvoort, who had, and still has, as its main objective recover and preserve the forest remnants of the region. The idea of environmental preservation was extended to family farmers of Turvo, which already had a tendency to sustainable production due to existence of faxinais in the region. This form was created to Coopaflora - Cooperativa de ProdutosAgroecologicos, Artesanais e Florestais the Turvo, who in partnership with the IAF, gives the family farmers the opportunity to cultivate and sell sustainable products. From this, we can observe the creation initiatives that seek to promote the permanence of family farming, faced with the advance of the modernization of agricultural techniques, through the dissemination and implementation of sustainable production models inherently compatible with the regional natural aspects.